Human and other critical factors in organizational learning in the hotel industry: A contingency approa - María del Mar Alonso-Almeida; Maria de la Soledad Celemín-Pedroche; Luis Rubio-Andrada; José Miguel Rodríguez-Antón (Tourism & Management Studies)
Organizational learning is instrumental to successful adaptation to today’s changing environment. Research on the subject in the context of the hotel industry is scant, however. The present study surveyed 147 Spanish hotels to determine the extent to which they drew from internal and external drivers and cultural and technological enablers and the level of organizational learning attained. These hotels were also characterized by the contingency factors most relevant to the industry and, based on the results, grouped into four clearly distinct clusters. An analysis of the groupings confirmed statistically significant inter-cluster differences. The empirical evidence gathered suggests that while all the hotel establishments studied stressed organizational learning, individual features determined differences in how successfully it is implemented. The inter-cluster differences identified suggest that the valuation of organizational learning varies with hotel type and, therefore, different organizational learning strategies must be implemented to attain higher performance.